Janis : Little Girl Blue [videorecording (DVD)] - Berg, Amy; Joplin, Janis; Cat Power, 1972- (2015)
Documentary on rock singer Janis Joplin, with her own words telling much of the story through a series of letters she wrote home over the years, read by Chan Marshall. Includes interviews with musicians P!nk, Kris Kristofferson, Melissa Etheridge, Bob Weir, Juliette Lewis, TV presenter Dick Cavett, filmmaker D.A. Pennebaker, the Joplin family, and others.